Student Voice, Teacher Professionalism, and Critical Pedagogy in Arabic Language Education: Insights from Indonesia - Frida Akmalia; Erna Andriyanti; Sulis Triyono (IRecall Journal, 2025)
Arabic language education in Indonesia occupies a distinctive position as both a sacred and heritage language, yet classroom pedagogy remains constrained by grammar-translation methods, exam-driven assessment, and hierarchical teacher–student relations. This article examines the intersections of student voice, teacher professionalism, and critical pedagogy in Arabic classrooms, highlighting their potential to reframe pedagogy in faith-based settings. Drawing on critical pedagogy (Freire, 1970) and democratic professionalism (Sachs, 2001), we synthesize international scholarship with the Indonesian context to propose a context-sensitive framework for integrating student perspectives. The analysis illustrates how curricular reforms (KMA No. 183/2019), digital tools, and dialogical practices create openings for student agency, while cultural hierarchies and exam orientations continue to constrain authentic participation. We argue that student voice in Arabic education not only enhances learner engagement and communicative competence but also reshapes teacher identity toward more reflective and dialogical professionalism. By situating these dynamics in Indonesia, this article offers insights into how student voice, teacher professionalism, and critical pedagogy converge in Arabic language education, extending global debates on multilingual and faith-based pedagogy.